Estudo de viabilidade técnica e econômica de sistema fotovoltaico híbrido com baterias na configuração Grid Zero - Almeida, Erick Santos de (Brasil, 2024)
This study evaluates the technical and economic strategies of a hybrid photovoltaic generation system with a battery bank, operating under the grid-zero strategy, for a house with an energy consumption of 49.89 kWh/d located in Manaus. This system aims to eliminate the injection of excess energy into the electrical grid, complying with current legislation and mitigating problems associated with the inversion of power flow, which occurs more frequently in larger systems or with excessive penetration of photovoltaic solar generation. Using the HOMER Pro software, simulations were performed to size the system components, evaluate its energy efficiency and estimate financial indicators, such as Net Present Cost (NPC), Return on Investment (ROI) and Payback. The results highlight the limited economic proposal of the hybrid system due to the high initial costs of components such as hybrid inverters and batteries. The system connected exclusively to the electrical grid presented the lowest NPC, of R$183,461.00, and the lowest Levelized Cost of Energy (COE), of R$0.870/kWh, being the most economical option. The inclusion of photovoltaic panels, with or without batteries, was tested at higher NPCs, although it provided greater energy sustainability and a significant renewable fraction, of up to 56.7%. The technical performance of the photovoltaic panels was developed, with an annual production of 18,365 kWh and a levelized cost of R$0.138/kWh, evidencing its efficiency in reducing dependence on the electrical grid. The battery bank, configured with 7 units, demonstrated high energy efficiency, and the average cost of R$0.451/kWh for stored energy, compromising its economic forecasts. It is concluded that, although the hybrid system offers greater energy independence and environmental benefits, its high initial cost and financial return limited its adoption in plans where economy is the determining factor. It is recommended that public policies and financial incentives be implemented to make hybrid technologies viable, aligning them with sustainability and energy transition goals in Brazil.